Synthesis of Dehydromuscone by an Alkene Metathesis Macrocyclization Reaction at 0.2 M Concentration - Garnes-Portolés, Francisco; Sánchez-Quesada, Jorge; Espinós-Ferri, Estela; Leyva-Pérez, Antonio (Synlett, 2022)
The industrial fragrance compound dehydromuscone was synthesized in five linear steps and 19% overall yield. The synthesis features a highly efficient nondiluted ring-closing metathesis macrocyclization reaction as a key step that proceeds at a 0.2 M concentration in the presence of 0.1 mol% Nitro-Grela catalyst. The synthesis employs commercially available linear starting materials and is shorter by at least two steps than the current industrial synthesis route.
Keywords: macrocyclization; dehydromuscone; Grela’s catalyst; fragrances; ring-closing metathesis; macrocycles